POWER CONTROL ERROR AND BER DETERMINATION IN MC-DS/CDMA SYSTEM OVER RAYLEIGH FADING CHANNEL USING WAVELET NETWORKS (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
This paper proposes an easy method based on wavelet networks for modeling the Bit Error Rate over a Rayleigh multipath fading channel taking care of a power control error. The RAKE receiver is considered for both coherent and non-coherent reception in this work when using a Weighted Despreading sequences for MAI cancellation in MC/DS-CDMA. It shows that the wavelet networks give a good reduction in term of complexity when calculating BER.